Organic matter and nutrient inputs from large wildlife influence ecosystem function in the Mara River, Africa - Amanda L. Subalusky; Christopher L. Dutton; Laban Njoroge; Emma J. Rosi; David M. Post (Ecology, 2018)
Animals can be important vectors for the movement of resources across ecosystem boundaries. Animals add resources to ecosystems primarily through egestion, excretion, and carcasses, and the stoichiometry and bioavailability of these inputs likely interact with characteristics of the recipient ecosystem to determine their effects on ecosystem function. We studied the influence of hippopotamus excretion/egestion and wildebeest carcasses, and their interactions with discharge, in the Mara River, Kenya. We measured nutrient dissolution and decomposition rates of wildlife inputs, the influence of inputs on nutrient concentrations and nutrient limitation in the river and the influence of inputs on biofilm growth and function in both experimental streams and along a gradient of inputs in the river. We found that hippopotamus excretion/egestion increases ammonium and coarse particulate organic matter in the river, and wildebeest carcasses increase ammonium, soluble reactive phosphorus, and total phosphorus. Concentrations of dissolved carbon and nutrients in the water column increased along a gradient of wildlife inputs and during low discharge, although concentrations of particulate carbon decreased during low discharge due to deposition on the river bottom. Autotrophs were nitrogen limited and heterotrophs were carbon limited and nitrogen and phosphorus colimited upstream of animal inputs but there was no nutrient limitation downstream of inputs. In experimental streams, hippo and wildebeest inputs together increased biofilm gross primary production ( GPP) and respiration ( R ). These results differed in the river, where low concentrations of hippo inputs increased gross primary production ( GPP ) and respiration ( R ) of biofilms, but high concentrations of hippo inputs in conjunction with wildebeest inputs decreased GPP . Our research shows that inputs from large wildlife alleviate nutrient limitation and stimulate ecosystem metabolism in the Mara River and that the extent to which these inputs subsidize the ecosystem is mediated by the quantity and quality of inputs and discharge of the river ecosystem. Thus, animal inputs provide an important ecological subsidy to this river, and animal inputs were likely important in many other rivers prior to the widespread extirpation of large wildlife.